Fed liftoff and subprime loan interest rates: Evidence from the peer-to-peer lending market - Christoph Bertsch; Isaiah Hull; Xin Zhang (Sveriges Riksbank, 2016)
On December 16th of 2015, the Fed initiated "liftoff," raising the federal funds rate range by 25 basis points and ending a 7-year regime of near-zero rates. We use a unique dataset of 640,000 loan-hour observations to measure the impact of liftoff on interest rates in the peer-to-peer lending segment of the subprime market. We find that the average interest rate dropped by 16.9-22.6 basis points. This holds for 14 and 28 day windows centered around liftoff, and is robust to the inclusion of a broad set of loan-level controls and fixed effects. We also find that the spread between high and low credit rating borrowers decreased by 16% and demonstrate that this was not generated by a change in the composition of borrowers along observable dimensions. Furthermore, we find no evidence that either result was driven by a collapse in demand for funds. Our results are consistent with an investor-perceived reduction in default probabilities; and suggest that liftoff provided a strong, positive signal about the future solvency of subprime borrowers, reducing their borrowing cost, even as short term rates increased in other markets.
Keywords: D14; E43; E52; G21; 330; peer-to-peer lending; subprime consumer loans; Fed liftoff; monetary policy signaling; default channel; household debt